Mechanistic Studies of Homo- and Heterodinuclear Zinc Phosphoesterase Mimics: What Has Been Learned? - Erxleben, Andrea (Frontiers in Chemistry, 2019)
Phosphoesterases hydrolyze the phosphorus oxygen bond of phosphomono-, di- or triesters and are involved in various important biological processes. Carboxylate and/or hydroxido-bridged dizinc sites are a widespread structural motif in this enzyme class. Much effort has been invested to unravel the mechanistic features that provide the enormous rate accelerations observed for enzymatic phosphate ester hydrolysis and much has been learned by using small and simple model systems for the biological dizinc sites. This review summarizes the knowledge and mechanistic understanding of phosphoesterases that has been gained from biomimetic dizinc complexes, showing the power as well as the limitations of model studies.